TNF-α disrupts the integrity of the porcine respiratory epithelial barrier. (June 2019) - Bercier, Philippe; Grenier, Daniel
Abstract: The airway epithelium plays an important role in protecting the host against environmental microbial pathogens. The disruption of the epithelial barrier may lead to inflammation and invasion by bacterial pathogens. The aim of the present study was to determine whether TNF-α can damage the integrity of the epithelial barrier using a tracheal epithelial cell model. TNF-α (10 and 100 ng/mL) significantly and time-dependently decreased the transepithelial electrical resistance of the epithelial barrier. The ability of TNF-α to disrupt epithelial barrier integrity was confirmed by quantifying the passage of fluorescein isothiocyanate-conjugated dextran across an epithelial monolayer. Immunofluorescence microscopy showed that TNF-α has a disruptive effect on both occludin and zonula occludens-1, which are important tight junction proteins. In addition to disrupting the epithelial barrier, TNF-α induced the secretion of IL-6 and IL-8 by tracheal epithelial cells. Lastly, incubating Gram-negative respiratory bacterial pathogens with the tracheal epithelial cells caused the cells to secrete TNF-α. In summary, the present study showed that TNF-α, which was secreted by the tracheal epithelial cells when they were stimulated with several swine pathogens, damaged tight junction proteins and disrupted the epithelial barrier of a pig tracheal epithelial cell model. TNF-α can also cause inflammation through its ability to induce IL-6 and IL-8 secretion by epithelial cells. Highlights: Tracheal epithelial cells secrete TNF-α in response to a challenge with several porcine bacterial pathogens. TNF-α damages tight junction proteins and disrupts the epithelial barrier of a porcine tracheal epithelial cell model. TNF-α induces the secretion of IL-6 and IL-8 by tracheal epithelial cells.